FORMULASI DAN UJI STABILITAS FISIK GEL EKSTRAK DAUN BINAHONG (Andredera cordifolia) - Surya Ningsi; Dwi Wahyuni Leboe; Sri Armaya (Universitas Islam Negeri Alauddin Makassar, 2016)
A research on the Formulation and Physical Stability Test Preparations Gel Binahong Leaf Extract (Andredera cordifolia). This study aims to determine the effect of the type and concentration of the base of the physical stability of the gel extracted using leaf samples binahong (Andredera cordifolia) by using 96% ethanol by maceration method. Gel formulation using 2 carbopol gel base is a base 940 and NaCMC. Each base is made in 3 concentration. Base is 0.5% carbopol 940, 1.25%, and 2%. NaCMC 3%, 4.5%, and 6% in addition to the base gel was also used as a negative control. Test is determined by observation of the organoleptic characteristics include color, smell, shape, pH probe, homogeneity inspection, test dispersive power, consistency test, test syneresis and viscosity determination. The results showed 940 carbopol gel with 1.25% concentration is shown in formula B is gelling who has the best physical stability for binahong leaf extract gel (Andredera cordifolia).